Global defects in collagen secretion in a Mia3/TANGO1 knockout mouse - Wilson, Deanna G. (The Rockefeller University Press, 2011)
Melanoma inhibitory activity member 3 (MIA3/TANGO1) is an evolutionarily conserved endoplasmic reticulum resident transmembrane protein. Recent in vitro studies have shown that it is required for the loading of collagen VII, but not collagen I, into COPII-coated transport vesicles. In this paper, we show that mice lacking Mia3 are defective for the secretion of numerous collagens, including collagens I, II, III, IV, VII, and IX, from chondrocytes, fibroblasts, endothelial cells, and mural cells. Collagen deposition by these cell types is abnormal, and extracellular matrix composition is compromised. These changes are associated with intracellular accumulation of collagen and the induction of a strong unfolded protein response, primarily within the developing skeleton. Chondrocyte maturation and bone mineralization are severely compromised in Mia3-null embryos, leading to dwarfism and neonatal lethality. Thus, Mia3’s role in protein secretion is much broader than previously realized, and it may, in fact, be required for the efficient secretion of all collagen molecules in higher organisms.